Locus of control, cognitive appraisal, and coping in stressful episodes. - Parkes, K (1984)
Evidence suggests that internals and externals differ in the nature and effectiveness of their coping behavior. This study investigated locus of control and coping processes in relation to specific stressful episodes reported by 171 female student nurses. Scores on each of three measures (General Coping, Direct Coping, and Suppression) that were derived from the "Ways of Coping" Questionnaire were analyzed to examine the role of appraisal (in terms of the extent to which the situation was perceived as amenable to control) and the perceived importance of the episode as mediators of the relation between locus of control and coping. The results showed significant interactions between locus of control and appraisal for each of the measures. Further examination of the interactions showed that the patterns of coping reported by internals were potentially more adaptive in relation to types of appraisal than those of externals. The perceived importance of the episode was significantly related, negatively, to suppression, but the interaction with locus of control was not significant.